Penerapan Kaidah Penulisan Artikel Ilmiah Dalam Penelitian Akuntansi: Penelitian - Cantika Olivia Yapardi; Najwa Azzahra; Rahel Lorensa Siburian; Sri Elfani Aulia Polem; Thalita Zahraini Dalimunthe; Syauqiyah Ramadani Asfa; Muhammad Anggie Januarsyah Daulay (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to comprehensively analyze and describe the application of effective and correct scientific article writing principles within the context of reporting accounting research findings. The importance of adhering to these principles lies in enhancing the quality, credibility, and readability of articles for acceptance in reputable scientific publications. Specifically, this research focuses on the standard article structure (Title, Abstract, Introduction, Method, Results and Discussion, and Conclusion), citation and referencing techniques, and the appropriate writing style for the accounting discipline. The method used in this research is descriptive qualitative with a content analysis approach. Primary data were collected through an in-depth literature review of various journal writing guidelines, published accounting scientific articles, and research methodology textbooks. Subsequently, a comparative analysis was conducted on the adherence to writing principles in a sample of published accounting articles. The results of this study are expected to serve as a practical guide for accounting researchers and students in composing their scholarly works.